Making Career Choices and Ai Based Career Counselling Model - Bikshalu, D.; Priyanka, T. Sai; Nikhitha, D.; Srihitha, B.; Jyothi, J.; Lekhana, M. (Journal of Neonatal Surgery, 2025)
Many advanced secondary students struggle to secure suitable employment during or after completing their education, which is a critical factor for long-term career satisfaction and personal fulfilment. This mismatch between students’ capabilities and their eventual career paths often leads to disengagement, lack of motivation, and unproductive professional lives. One of the core reasons behind this issue is the absence of structured and effective career guidance within educational systems. Career development services are either inadequate or inaccessible to many, leaving students to make uninformed decisions based on limited exposure or social pressure. In this context, Artificial Intelligence (AI) offers a transformative solution. With its ability to simulate expert-level interactions and deliver tailored guidance, AI can bridge the gap left by the shortage of qualified career counsellors. By analyzing a student’s interests, strengths, preferences, and even behavioral patterns, AI-powered systems can offer personalized career recommendations and learning pathways. This technology is especially beneficial in resource-constrained settings where human guidance is limited or unavailable